Association between serum uric acid/serum creatinine ratios and lung function in the general American population: National Health and Nutrition Examination Survey (NHANES), 2007–2012. Issue 1 (7th March 2023) - Wen, Jun; Wei, Chengcheng; Giri, Mohan; Zhuang, Rongjuan; Shuliang, Guo
Abstract : Background: Assessment of lung function is essential for the early screening chronic airway diseases (CADs). Nevertheless, it is still not widely used for early diagnosing CADs in epidemiological or primary care settings. Thus, we used data from the US National Health and Nutrition Examination Survey (NHANES) to discuss the relationship between the serum uric acid/serum creatinine (SUA/SCr) ratio and lung function in general adults to gain the role of SUA/SCr in early assessment of lung function abnormalities. Methods: From 2007 to 2012 NHANES, a total of 9569 people were included in our study. Using the regression model, XGBoost algorithm model, generalised linear model and two-piecewise linear regression model, the link between the SUA/SCr ratio and lung function was investigated. Results: After correcting for confounding variables, the data revealed that forced vital capacity (FVC) declined by 47.630 and forced expiratory volume in one second (FEV1) decreased by 36.956 for each additional unit of SUA/SCr ratio. However, there was no association between SUA/SCr and FEV1/FVC. In the XGBoost model of FVC, the top five most important were glycohaemoglobin, total bilirubin, SUA/SCr, total cholesterol and aspartate aminotransferase, whereas in FEV1, were glycohaemoglobin, total bilirubin, total cholesterol, SUA/SCr and serum calcium. In addition, we determined the linear and inverse association between SUA/SCr ratio and FVC or FEV1 by constructing a smooth curve. Conclusions: In the general American population, the SUA/SCr ratio is inversely linked with FVC and FEV1, but not with FEV1/FVC, according to our research. Future studies should investigate the impact of SUA/SCr on lung function and identify possible mechanisms of action.